CISCO 2900 SWITCH CONFIGURATION ANALYSIS SERIES ON LOCAL AREA NETWORK (LAN) OPERATING SYSTEM WITH NT 2000 - Sugandi Sugandi; Fivtatianti, Skom, MM Fivtatianti, Skom, MM (Jurnal Sistem Komputer, 2004)
Cisco switches are devices that have a higher intelligence level compared to the hub, switch, Cisco has a translation table, which automatically creates a list of MAC address (Media Access Control). Of all the computers connected to the switch, cisco switch therefore can reduce network traffic by only broadcast news (broadcast). Similarly, each port on the switch has a collision domain (Containers collision) on their own, in this case Cisco switches to create a Virtual Private Network (VPN) from the port of the sender to the receiver port so that if the two computers are communicating through the VPN, if one port is busy Other ports can still function. Therefore, Cisco switches can enlarge the network bandwidth.